Effectiveness of Tai Chi on Blood Pressure, Stress, Fatigue, and Sleep Quality among Chinese Women with Episodic Migraine: A Randomised Controlled Trial. (19th October 2022) - Wang, Shuting; Tian, Longben; Ma, Tongyu; Wong, Yuen Ting; Yan, Lin Jia; Gao, Yang; Zhang, Dexing; Hui, Stanley Sai-Chuen; Xie, Yao Jie
Abstract : The beneficial effects of Tai Chi on the cardiovascular risk profile and the migraine trigger factors among female migraineurs remain unknown. This study aimed to evaluate the effectiveness of a 12-week Tai Chi training on blood pressure (BP) and migraine-related trigger factors, including stress, fatigue, and sleep quality among Chinese women with episodic migraine. In this study, eligible Hong Kong Chinese women aged 18–65 years were randomly assigned to the Tai Chi group adopting a modified 33-short form of Yang style Tai Chi training for 12 weeks, followed by additional 12 weeks of self-practice or the waiting list control group that maintained the usual lifestyle for 24 weeks. The primary outcome was the changes in BP from the baseline to 12 and 24 weeks. The secondary outcomes included the stress level, fatigue, and sleep quality measured by the perceived stress scale (PSS), the numeric rating scale-fatigue (NRS-fatigue), and the Pittsburgh sleep quality index (PSQI), respectively. Significant between-group differences were found in systolic BP (−6.8 mmHg at 24 weeks, P = 0.02 ), and a decreasing trend was significant across baseline, 12 weeks, and 24 weeks between groups (P < 0.05 ). The 12-week Tai Chi training significantly reduced the BP level and moderately improved stress level, fatigue status, and sleep quality among Chinese women with episodic migraine. Therefore, Tai Chi could be considered a promising mind-body exercise with good feasibility for migraineurs in the future. This trial is registered with registration number NCT03015753 .